2018
DOI: 10.1080/14656566.2018.1491549
|View full text |Cite
|
Sign up to set email alerts
|

Methylnaltrexone bromide for the treatment of opioid-induced constipation

Abstract: The extensive and alarming use of opioids for pain management in patients with chronic pain receiving palliative care is associated with non-tolerable gastrointestinal (GI) adverse effects. Opioid-induced constipation (OIC) is the most common adverse effect impairing patient quality of life (QOL). In addition, OIC is one of the treatment limiting consequences of opioid analgesics. Management of OIC is becoming a challenge since traditional laxatives have limited efficiency. Peripherally acting mu-opioid recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 57 publications
3
6
0
Order By: Relevance
“…These results are similar to those found in studies of subcutaneous methylnaltrexone in adult populations with chronic OIC and pediatric oncology patients. [6][7][8][9]16 Our results support the postoperative use of methylnaltrexone in pediatric populations with acute OIC after PSF with no appreciable side effects.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…These results are similar to those found in studies of subcutaneous methylnaltrexone in adult populations with chronic OIC and pediatric oncology patients. [6][7][8][9]16 Our results support the postoperative use of methylnaltrexone in pediatric populations with acute OIC after PSF with no appreciable side effects.…”
Section: Discussionsupporting
confidence: 69%
“…Evidence in adult studies has shown methylnaltrexone to be significantly more effective than placebo in treating OIC in patients with cancer and chronic noncancer pain. 6,7 A small randomized placebo-controlled phase 2 study showed promise in the use of subcutaneous methylnaltrexone for the treatment of acute OIC after orthopaedic surgery. 14 In a study of adults with chronic noncancer pain, the efficacy of methylnaltrexone for the treatment of OIC was demonstrated with a comparable safety profile to placebo administration with no evidence of cardiac toxicity or opioid withdrawal symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a quaternary ammonium compound with a positive charge, which restricts its ability to cross the BBB. 24 Naloxegol [Movantik ® (US), Moventig ® (EU), previously NKTR-118] was the first orally administered PAMORA. It is a polyethylene glycol (PEG) derivative of naloxone.…”
Section: Opioid Receptors Localization and Activity In The Ensmentioning
confidence: 99%
“…31 Another minor metabolite, naldemedine-(7R)-7-hydroxide, is formed after oxidation of naldemedine. In the GI tract, enterobacteria cleave the parent compound, starting by reducing its oxadiazole portion and hydrolyzing the remaining amide bond to form benzamidine and naldemedine carboxylic acid 22,24 which are excreted in both urine and feces.…”
Section: Pharmacokineticsmentioning
confidence: 99%